OPTIMASI PENDAPATAN: Strategi Kreatif Pemerintah Kota Kendari melalui Pajak Reklame Bersama Badan Pendapatan Daerah - Suriyani BB; Makmur Kambolong; La Ode Muhammmad Elwan (Journal Publicuho, 2023)
This study aims to determine the strategy of the Kendari City government in increasing local revenue (PAD) through the advertisement tax and to determine the flow of billing tax collection to increase local revenue (PAD) in Kendari City. The method used in this research is a descriptive qualitative research method using observation, interviews and documentation. The informants in this study were 7 people. The results of this study indicate that the Kendari City government's strategy in increasing local revenue (PAD) through advertisement taxes carried out by the Regional Revenue Agency through intensification and extensification strategies and the collection flow has been going quite well, this is indicated by an increase in local taxes every year. Streamline and streamline collection through increasing the number of taxpayers, increasing outreach activities to the community every quarter or 1 year 4 times to raise public awareness that paying taxes and regional levies is in accordance with what is done by BAPENDA Kendari City.